Local Wisdom of Religion, Culture and Economy of the Community of Kampung Dukuh, Garut, West Java - Ira Siti Rohmah Maulida; Mamat Rachmat Effendi; Ifa Hanifia Senjiati (Global Writing Academica Researching and Publishing, 2022)
This study describes how the interdependence of religion and culture on the economy of the indigenous people of Kampung Dukuh. The indigenous community of Kampung Dukuh has its uniqueness when compared to other indigenous communities, especially in terms of “religiousness expressed in local wisdom.” The indigenous people of Kampung Dukuh tend to make